Fast food over safe food? A qualitative evaluation of a food safety training intervention for street vendors applying the COM-B model in Ouagadougou, Burkina Faso - Madjdian, D.S.; Badu, V.D.; Ilboudo, Guy S.; Lallogo, Valerie R.; Dione, Michel M.; Asseldonk, M. van; Knight-Jones, Theodore J.D.; Vet, E. de (2024)
The safety of ready-to-eat food sold in urban informal markets in low and middle-income countries is a pressing public health challenge, that needs to be addressed if we are to establish healthy food systems. Guided by the Capability, Opportunity, and Motivation model for Behavior change (COM-B), this qualitative study aimed to explore perceptions of street vendors on their participation in a food safety capacity building intervention, consisting of training and provision of food safety equipment. The intervention aimed to improve food safety behavior of vendors of ready-to-eat chicken in informal markets in Ouagadougou, Burkina Faso. A total of 24 vendors selling ready-to-eat chicken at street restaurants participated in semi-structured interviews after training, which focused on vendors’ stories of change related to food safety capabilities, opportunities, motivation, and behaviors. Data were thematically analyzed following COM-B components. Vendors noted improvements in psychological (i.e., knowledge, awareness, self-efficacy, perceptions) and physical capabilities (i.e., equipment useability and applicability), and motivations (perceived responsibility, reputation, client satisfaction, profits, consumer demand). Moreover, training and provision of equipment, spill-over effects to employees or neighboring outlets, and social support were perceived as key social and physical opportunities, while structural challenges such as market infrastructure, regulations, financial resources, cost of living, and outlet culture were physical barriers to implement lessons learnt. This study provides insights into the impact of engaging vendors in improving food safety behavior through training and equipment provision. Improvements in vendors’ perceived capabilities and motivation contributed to improved food safety behavior, while contextual barriers hindered the perceived adoption of food safety behaviors.